2020
DOI: 10.1038/s41598-020-60443-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lung Catalase Activity Confers Protection Against Experimental RSV Infection

Abstract: Respiratory syncytial virus (RSV) infection in mouse and human lung is associated with oxidative injury and pathogenic inflammation. RSV impairs antioxidant responses by increasing the degradation of transcription factor NRF2, which controls the expression of several antioxidant enzyme (AOE) genes, including catalase. Since catalase is a key enzyme for the dismutation of virus-mediated generation of hydrogen peroxide (H 2 o 2) we developed a model of intranasal supplementation of polyethylene glycol-conjugated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
(34 reference statements)
0
23
0
2
Order By: Relevance
“…In addition, TNF-TNFR1 binding generates intracellular reactive oxygen species (ROS) that in-turn further upregulate the wide-spread expression of TNFR1 on the cell surface [ 50 , 51 ]. RSV is known to significantly enhance ROS production, and previous studies in our lab have demonstrated that both controlling ROS generation and increasing antioxidant capacity in the lung leads to improved clinical parameters in mice, including body weight loss, illness score, and bronchoconstriction, in association with a significant reduction in TNF-α in the BALF [ 52 , 53 ]. Collectively, this suggests the TNF-TNFR1 interaction may be a key initial event that leads to airway narrowing and clinical manifestations of RSV infections, supporting interference of TNFR1 as a new potential therapeutic strategy for RSV bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-TNFR1 binding generates intracellular reactive oxygen species (ROS) that in-turn further upregulate the wide-spread expression of TNFR1 on the cell surface [ 50 , 51 ]. RSV is known to significantly enhance ROS production, and previous studies in our lab have demonstrated that both controlling ROS generation and increasing antioxidant capacity in the lung leads to improved clinical parameters in mice, including body weight loss, illness score, and bronchoconstriction, in association with a significant reduction in TNF-α in the BALF [ 52 , 53 ]. Collectively, this suggests the TNF-TNFR1 interaction may be a key initial event that leads to airway narrowing and clinical manifestations of RSV infections, supporting interference of TNFR1 as a new potential therapeutic strategy for RSV bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous administration of catalase has been shown to mitigate respiratory viral infections. Intranasal catalase protected against respiratory syncytial virus (RSV) infection [ 63 ], a virus that can induce a cytokine storm [ 64 ]. Catalase treatment led to a significant reduction in the levels of the cytokines IL-1 α , TNF- α , and IL-9 and the chemokines CSCL1, CCL2, and CCL5 [ 63 ].…”
Section: R-bhb Decreases Ros/rns Levels As a Mechanism To Blunt Thmentioning
confidence: 99%
“…Intranasal catalase protected against respiratory syncytial virus (RSV) infection [ 63 ], a virus that can induce a cytokine storm [ 64 ]. Catalase treatment led to a significant reduction in the levels of the cytokines IL-1 α , TNF- α , and IL-9 and the chemokines CSCL1, CCL2, and CCL5 [ 63 ]. During the early stages of other types of respiratory infections, increased ROS activates the nuclear factor erythroid 2-related factor 2 (NFE2L2 commonly called Nrf2) transcriptional regulator to induce antioxidant genes such as SOD3 and catalase to protect against the ROS-induced proinflammatory gene expression and subsequent cytokine storm.…”
Section: R-bhb Decreases Ros/rns Levels As a Mechanism To Blunt Thmentioning
confidence: 99%
“…To test whether this disruption of this antioxidant pathway was relevant to disease progression, SOD mimetics and stabilized polyethylene glycol-conjugated catalase were administered in an experimental rodent model of RSV infection [107,108]. These manipulations resulted in reduced viral H 2 O 2 production and produced a significant protective effect on RSV-induced inflammation, clinical disease and airway pathology.…”
Section: Rsv Depletion Of Antioxidant Capacity Is Linked To Disease Pathogenesismentioning
confidence: 99%